To find the distance between the points \((3, -5)\) and \((-2, -7)\), we can use the distance formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Let's plug in the values where \((x_1, y_1) = (3, -5)\) and \((x_2, y_2) = (-2, -7)\):
\[ d = \sqrt{((-2) - 3)^2 + ((-7) - (-5))^2} \]
Calculating the differences:
\[ d = \sqrt{(-5)^2 + (-2)^2} \]
Calculating the squares:
\[ d = \sqrt{25 + 4} = \sqrt{29} \]
Now we can calculate \(\sqrt{29}\):
\[ \sqrt{29} \approx 5.385 \]
Rounding this to the nearest tenth gives us:
\[ 5.4 \]
Thus, the distance between the two points, rounded up to the nearest tenth, is about 5.4 units.